2002
DOI: 10.3168/jds.s0022-0302(02)74318-x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Inbreeding by Constraining the Average Relationship Between Parents of Young Bulls Entering AI Progeny Test Programs

Abstract: In breeding is known to impair the health, fertility, and productivity of dairy cattle and other livestock species. Mating programs can address inbreeding concerns on the farm, at least in the short term, but long-term control of inbreeding in a dairy population requires consideration of relationships between young bulls entering AI progeny test programs. The present study discusses an application of optimal contribution methodology to selection of young AI bulls in the five major US dairy breeds. Elite cows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
2
29
1
Order By: Relevance
“…The main relationship between selected bulls decreased from 0.393 to 0.308, but selection response was slightly lower (1.098 vs. 1.054). Weigel and Lin (2002) used the method of Meuwissen (1997) and constrained the level of inbreeding in the next generation and found that the optimal number of bull sires and bull dams decreased as the inbreeding constraint increased, particularly at low levels of inbreeding. Weigel and Lin (2000) compared the weighted mean lifetime net merit and the weighted mean adjusted lifetime net merit of the selected group.…”
Section: Optimum Genetic Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main relationship between selected bulls decreased from 0.393 to 0.308, but selection response was slightly lower (1.098 vs. 1.054). Weigel and Lin (2002) used the method of Meuwissen (1997) and constrained the level of inbreeding in the next generation and found that the optimal number of bull sires and bull dams decreased as the inbreeding constraint increased, particularly at low levels of inbreeding. Weigel and Lin (2000) compared the weighted mean lifetime net merit and the weighted mean adjusted lifetime net merit of the selected group.…”
Section: Optimum Genetic Contributionsmentioning
confidence: 99%
“…Further on, Sonesson and Meuwissen (2000) developed an algorithm to combine OGC results with specific mating strategies. In dairy cattle, OGC was applied in the United Kingdom Holstein population (Kearney et al, 2004) and in different breeds in the United States (Weigel and Lin, 2002) for matings between bull sires and bull dams. They found increased genetic gain at the same rate of inbreeding compared to traditional selection schemes.…”
Section: Introductionmentioning
confidence: 99%
“…In research on non-endangered commercial cattle breeds (Ayrshire, Brown Swiss, Guernsey, Holstein and Jersey), Weigel and Lin (2002) address the use of restrictions on the increase of inbreeding in the selection of AI bulls. They find that the reduction in genetic gain is mainly due to the reduction in the selection intensity through the use of more parents, not because of the selection of genetically inferior animals.…”
Section: Practical Applications Of Pedigree-based Managementmentioning
confidence: 99%
“…(Nomura et al, 2001;Weigel & Lin, 2002;Gutiérrez et al, 2003;Chikhi et al, 2004;Hagger, 2005). Unfavorable effects of inbreeding on milk yield and lactation length , and on weaning and yearling weights (Queiroz et al, 2000) were reported for Gyr cattle.…”
Section: Introductionmentioning
confidence: 99%